Oral administration of Clostridium butyricum CGMCC0313‐1 reduces ovalbumin‐induced allergic airway inflammation in mice. Issue 5 (25th January 2017) - Juan, Zhang; Zhao‐Ling, Shi; Ming‐Hua, Zeng; Chun, Wei; Hai‐Xia, Wu; Meng‐Yun, Liu; Jian‐Qiong, Huang; Yue‐Jie, Zheng; Xin, Sun
ABSTRACT: Background and objective: Probiotic bacteria can induce immune regulation or immune tolerance in patients with allergic diseases, but the underlying mechanisms are still unclear. There has been a growing interest in the use of beneficial bacteria for allergic diseases recently. This study aimed at exploring whether Clostridium butyricum CGMCC0313‐1 ( C. butyricum ) can reduce ovalbumin (OVA)‐induced allergic airway inflammation in a mouse model. Methods: Mouse model of allergic airway inflammation induced via OVA was used in this study. C. butyricum was administered daily by the oral route during or after the sensitization. Airway function, pulmonary airway inflammation, mast cell degranulation, T helper (Th)‐specific and anti‐inflammatory cytokines, OVA‐specific Ig, matrix metalloproteinase 9 (MMP‐9) and histopathological alterations were examined. Results: C. butyricum significantly reduced lung resistance in the asthmatic mice. Pulmonary airway inflammation, mast cell degranulation, airway remodelling and the expression of OVA‐specific IgE/G1 were suppressed by oral C . butyricum . It also reversed the imbalance of Th1/Th2 and increased the anti‐inflammatory cytokine IL‐10. Conclusion: C . butyricum reduces OVA‐induced allergic airway inflammation in mice and might be an additional or supplementary therapy for allergic asthma. Abstract : Clostridium butyricum CGMCC0313‐1 ( C. butyricum ) was administered orally to mouse models of allergic airways disease. We found that C. butyricum can reduce ovalbumin (OVA)‐induced allergic airway inflammation in mice.